The Origin and Reversible Nature of Poultry Litter Biochar Hydrophobicity. Issue 3 (1st May 2015) - Yi, Susan; Witt, Brandon; Chiu, Pei; Guo, Mingxin; Imhoff, Paul
Abstract : Transient changes in wettability complicate the prediction of biochar's hydrologic effects. Biochar wetting properties were characterized from poultry litter biochar (PLBC) produced from slow pyrolysis at temperatures between 300 and 600°C with water drop penetration time (persistence of hydrophobicity) and contact angle (CA; severity of hydrophobicity) measurements. Hydrophobicity was associated with semivolatile organic compounds coating PLBC surfaces, which resulted in 24.4 carbon layers and CAs of 101.1 ± 2.9° at a pyrolysis temperature of 300°C but only 0.4 layers of surface coverage and CAs of 20.6 ± 1.3° when pyrolyzed at 600°C. Mixing PLBC with water removed organic coatings, and storage in water for 72 h decreased CA as much as 81° for the most hydrophobic PLBCs. When mixed with quartz sand of the same particle size, CAs of PLBC–sand mixtures increased from 6.6 ± 1.4° at 0% PLBC mass fraction to 48.3 ± 2.0° at 15% mass fraction. Hydrophobic and hydrophilic PLBCs increased CA by nearly identical amounts at 2 and 5% mass fractions, which was explained by the influence of PLBC particle topology on macroscopic surface roughness of PLBC–sand mixtures. For environmentally relevant situations, PLBC–sand mixtures at mass fractions ≤15% remained water wetting. However, all PLBC additions increased CA, which may alter infiltration rates and induce preferential water flow.